Building a measure of the quality of performance of school sports activity members in Iraq from the point of view of the employees of the Ministry of Education (Journal of the College of Basic Education, 2022)
The problem of the current research lies in answering the following question:Is it possible to provide a tool through which to build quality measures of school sports activity performance in Iraq?The study aims to:Building a performance quality measure for school sports activity affiliates in Iraq from the point of view of the Ministry of Education employees.Establishing standard levels and grades for school sports activity affiliates in Iraq from the point of view of the Ministry of Education employees.The researcher used the descriptive approach in the survey method, and identified the research community of the employees of the General Directorate of Educational Supervision / Department of Specialized Supervision in the Ministry of Education, and those in the General Directorate of Physical Education and School Activity / Department of School Sports in the Ministry of Education, who numbered (81) members, and the community was divided into a sample A construction and an application sample, and the researchers built the scale based on the stages of building the scale in a scientific manner, and divided the scale into axes and each axis includes a set of paragraphs related to the axis and serves the purpose of the scale. As required by the results and serve the objectives of the study.In his study, the researcher reached a number of results, the most important of which are:1- The researchers reached a measure of the quality of performance of school sports activity in Iraq from the point of view of the employees of the Ministry of Education.2- Standard levels and degrees have been set to measure the quality of school sports activity performance in Iraq from the point of view of the employees of the Ministry of Education